Lightweight high-strength composite wave-absorbing material and preparation method thereof

By combining hollow glass microspheres with metal sulfide composite shells, the problem of poor structural stability of metal sulfide hollow microspheres has been solved, achieving lightweight and efficient preparation, and yielding a microwave absorbing material with low density, high strength and excellent dielectric loss.

CN117977220BActive Publication Date: 2026-11-03TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211309091.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2026-11-03
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

In the existing technology, the hollow microsphere structure of metal sulfide has poor stability during the preparation process, which leads to unstable performance of microwave absorbing materials and makes them difficult to mass-produce.

Method used

A composite microwave absorbing material combining hollow glass microspheres and metal sulfide composite shells is prepared by high-temperature combustion and reducing atmosphere calcination to form a fusion interface between the glass microspheres and the metal sulfide composite shells, achieving structural stability and high dielectric loss.

Benefits of technology

The prepared composite absorbing material has low density, high strength and excellent dielectric loss properties, and the preparation method is simple and easy to mass-produce.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117977220B_ABST
    Figure CN117977220B_ABST
Patent Text Reader

Abstract

The application discloses a light-weight high-strength composite wave-absorbing material and a preparation method thereof. The composite wave-absorbing material is a hollow microsphere. The structure comprises hollow glass microspheres and a metal sulfide composite shell combined on the hollow glass microspheres. Part of the combination interface between the hollow glass microspheres and the metal sulfide composite shell is fused. The application solves the problems of poor stability of the metal sulfide composite microsphere structure wave-absorbing material and complex preparation conditions which are not suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of microwave absorbing agent preparation technology. More specifically, it relates to a lightweight, high-strength composite microwave absorbing material and its preparation method. Background Technology

[0002] Microwave-absorbing materials are widely used for electromagnetic wave absorption and (primarily absorption-mechanism-driven) shielding, thereby controlling electromagnetic pollution and improving the low-electromagnetic-wave detectability of equipment. The electromagnetic wave absorber (absorbing agent) in these materials is crucial in determining their electromagnetic properties and application effectiveness. To improve the performance of microwave-absorbing materials, the absorbing agent needs to maintain a high addition ratio and form a specific spatial distribution to ensure high electromagnetic wave loss capability and avoid inhomogeneity and weakened impedance matching caused by component segregation. Based on these considerations, hollow microsphere electromagnetic wave absorbers have attracted increasing attention from researchers and technology developers. The reasons can be attributed to four aspects: First, the cavity of the hollow microspheres can endow the microwave absorber with low density, and the overall low density of the microwave absorber can still be maintained even when filled in a high proportion; second, the hollow structure can achieve density matching with the polymer matrix by adjusting the ratio of inner and outer diameters and the spherical shell structure, avoiding component segregation during the molding process of the microwave absorber; third, the spherical appearance is conducive to dispersing external stress, avoiding structural damage and loss of further excellent properties due to stress concentration; fourth, the spherical appearance can also endow the microsphere microwave absorber with high fluidity and filling characteristics, so as not to significantly increase the viscosity of the composite system and the resulting structural inhomogeneity when added in a large proportion.

[0003] Metal sulfides are dielectric microwave absorbing agents with advantages such as abundant natural reserves, highly designable crystal forms, good environmental stability, and easy control over crystal structure and defect design. Similar to other microwave absorbing agents, the increasing demand for lightweight advanced microwave absorbing agents (especially for aerospace applications) presents challenges. The high density of metal sulfide microwave absorbing agents increases the difficulty of material preparation and the overall high density remains a critical issue. Constructing micro / nano hollow structures of metal sulfides is an effective way to achieve lightweighting. Researchers have developed various hollow metal sulfide structures for design and controlled synthesis, with hollow microspheres being the most common. However, maintaining the structural stability of these hollow metal sulfide microspheres is crucial, both in the preparation of test samples during research and in practical applications when compounded with polymers and other composite materials. On the one hand, maintaining the stability of the hollow microsphere structure during testing is crucial for accurately obtaining the performance parameters of this type of microwave absorber, effectively guiding technological development practices. On the other hand, the efficient maintenance of the hollow microsphere structure during practical application is a key factor affecting the effectiveness of the process and ensuring the product's performance (lightweight design, electromagnetic parameters). Furthermore, the preparation methods for metal sulfide hollow microsphere materials still suffer from drawbacks such as cumbersome processes, the need for special environments or additives, and limitations on mass production. Therefore, designing highly stable metal sulfide composite microsphere structures and achieving efficient preparation through suitable mass production methods remains a significant challenge for the development of lightweight hollow microsphere metal sulfide microwave absorbers. Summary of the Invention

[0004] To address the above problems, the present invention aims to provide a lightweight, high-strength composite microwave absorbing material and its preparation method. This solves the problems of poor stability and complex preparation conditions that hinder mass production in microwave absorbing materials with metal sulfide composite microsphere structures.

[0005] To achieve the above objectives, the present invention adopts the following technical solution:

[0006] On the one hand, the present invention provides a lightweight and high-strength composite microwave absorbing material, which is a hollow microsphere; its structure includes hollow glass microspheres and a metal sulfide composite spherical shell bonded to the hollow glass microspheres;

[0007] In this composite absorbing material, there is partial fusion at the interface between the hollow glass microspheres and the metal sulfide composite shell.

[0008] Furthermore, the density of the hollow microspheres is 0.4-1.5 g / cm³. 3 Particle size 6-120 micrometers.

[0009] Furthermore, the shell of the hollow glass microsphere is a silicate glass shell with a thickness of 200-1200 nanometers.

[0010] Furthermore, the thickness of the metal sulfide composite spherical shell is 20-1000 nanometers.

[0011] Furthermore, in the metal sulfide composite spherical shell, the metal component is selected from one or more of iron, cobalt, nickel, copper, or molybdenum.

[0012] Furthermore, in the metal sulfide composite spherical shell, the metal component is selected from at least two of iron, cobalt, nickel, copper, or molybdenum. This results in a microwave absorbing material with superior performance.

[0013] In another aspect, the present invention provides a method for preparing the composite absorbing material as described above, comprising the following steps:

[0014] Metal salts and organic fuels are dissolved in deionized water, hollow glass microspheres are added, and the mixture is stirred evenly to obtain a precursor solution.

[0015] The above precursor liquid was placed in a high-temperature muffle furnace for combustion reaction, and hollow microspheres A were obtained by sieving.

[0016] The hollow microspheres A were calcined in a reducing atmosphere to obtain hollow microspheres B;

[0017] The hollow microspheres B were mixed evenly with sulfur powder and calcined in an inert atmosphere to obtain the composite microwave absorbing material.

[0018] In the above preparation method, during the combustion reaction of the precursor liquid in a high-temperature muffle furnace to form hollow microspheres A, the combustion reaction process promotes the partial fusion of the interface between the final product hollow glass microspheres and the metal sulfide composite shell, without a clear boundary line.

[0019] Furthermore, the metal salt is an organic or inorganic salt of a metal.

[0020] Furthermore, the concentration of the metal salt in the precursor solution is 2-15 mol / L.

[0021] Furthermore, in the precursor solution, the molar ratio of the organic fuel to the metal salt is 1-4.

[0022] Furthermore, the organic fuel is selected from one or more of citric acid, glycine, urea, or ethylene glycol.

[0023] Furthermore, in the precursor solution, the mass concentration of the hollow glass microspheres is 0.35-1.5 g / mL.

[0024] Furthermore, the combustion reaction takes place in an air atmosphere, and the combustion reaction temperature is 300-800℃, with a time of 5-40 minutes. Exemplary combustion reaction temperatures include, but are not limited to, 300-600℃, 300-500℃, 500-800℃, 500-600℃, 600-800℃, 300℃, 500℃, 600℃, and 800℃.

[0025] Further, the metal salt is selected from a mixture of ferric nitrate and cobalt nitrate, and the organic dye is selected from citric acid. For example, the molar ratio of ferric nitrate, cobalt nitrate, and citric acid is (1-2):1:(4-9). In this case, the material exhibits good stability and microwave absorption. For example, the molar ratio of ferric nitrate, cobalt nitrate, and citric acid is 2:1:6, 1:1:4, 2:1:9, etc.

[0026] Furthermore, the metal salt includes a soluble salt of iron. Exemplary soluble salts of iron are selected from ferric nitrate, ferric chloride, and ferric sulfate.

[0027] Furthermore, the metal salt includes a cobalt-soluble salt. Exemplary cobalt-soluble salts are selected from cobalt chloride, cobalt sulfate, cobalt acetate, and cobalt nitrate.

[0028] Furthermore, the metal salt includes a copper-soluble salt, such as copper nitrate.

[0029] Furthermore, the metal salt includes a nickel-soluble salt, such as nickel nitrate.

[0030] Furthermore, the metal salt includes a soluble salt of molybdenum, such as ammonium heptamolybdate.

[0031] Furthermore, the sieving process is performed using a 35-350 mesh standard sieve.

[0032] Furthermore, the calcination temperature in the reducing atmosphere is 500-700℃, and the holding time is 1-5 hours. The study found that if the calcination temperature in the reducing atmosphere is too low, the reduction is incomplete; if the reduction temperature is too high, the resulting microspheres have poor surface morphology and poor stability. Preferably, the calcination temperature in the reducing atmosphere is 620-650℃, at which point the microwave absorption performance is better. For example, the calcination temperature in the reducing atmosphere is 650℃.

[0033] Furthermore, the sulfur powder is sublimed sulfur. Sublimed sulfur has high purity, small molecular weight, and high reactivity.

[0034] Further, the mass ratio of sulfur powder to hollow microspheres B is 1:20-1:3. For example, the mass ratio of sulfur powder to hollow microspheres B includes, but is not limited to, 1:10-1:3, 1:8-1:3, 1:5-1:3, 1:4-1:3, 1:10-1:4, 1:8-1:4, 1:5-1:4, 1:10-1:5, 1:8-1:5, 1:10-1:8, 1:10, 1:8, 1:5, 1:4, 1:3, etc.

[0035] Furthermore, the calcination temperature in the inert atmosphere is 300-700℃, and the time is 2-4 hours. Calcination in the inert atmosphere is the process of carrying out a sulfidation reaction. For example, the calcination temperature in the inert atmosphere can be 300-500℃, 300-400℃, 500-700℃, 400-700℃, 400-500℃, 300℃, 400℃, 500℃, 700℃, etc.

[0036] The beneficial effects of this invention are as follows:

[0037] In the composite absorbing material provided by this invention, a large proportion of cavities within the structure achieves low density, the glass spherical shell provides high-strength support, and the metal sulfide composite spherical shell provides high dielectric loss. Simultaneously, the interface fusion between the glass spherical shell and the metal sulfide composite spherical shell endows the structure with better overall structural stability and high dielectric loss.

[0038] The preparation method provided by this invention is simple, and the composite absorbing material prepared by this method has a unique structure, good overall structural stability, and high dielectric loss. Attached Figure Description

[0039] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.

[0040] Figure 1 The diagram shows the structure of the lightweight and high-strength composite microwave absorbing material of the present invention.

[0041] Figure 2 A schematic diagram showing the preparation process of the lightweight and high-strength composite microwave absorbing material of the present invention is shown.

[0042] Figure 3 Single-sphere scanning electron microscope image of the glass / sulfide composite hollow microspheres obtained in Example 1.

[0043] Figure 4 Cross-sectional scanning electron microscope image of the glass / sulfide composite hollow microspheres obtained in Example 1.

[0044] Figure 5 XRD pattern of the glass / sulfide composite hollow microspheres prepared in Example 1.

[0045] Figure 6 Microwave absorption performance of the glass / sulfide composite hollow microspheres prepared in Example 1. Detailed Implementation

[0046] To more clearly illustrate the present invention, the following description, in conjunction with preferred embodiments and accompanying drawings, further explains the invention. Similar components in the drawings are indicated by the same reference numerals. Those skilled in the art should understand that the specific description below is illustrative rather than restrictive and should not be construed as limiting the scope of protection of the present invention.

[0047] Example 1

[0048] Glass / sulfide composite hollow microspheres with microwave absorption properties have a structure as follows: Figure 1 As shown, its preparation method is as follows: Figure 2 As shown, the specific preparation method is as follows:

[0049] A density of 0.38 g / cm³ was used. 3 Commercial silicate glass hollow microspheres.

[0050] Weigh 8.08g Fe(NO3)3·9H2O, 2.91g Co(NO3)2·6H2O, and 12.61g C6H8O7·H2O into a 100mL beaker, add 3.5g deionized water, heat in a 35℃ water bath, and stir magnetically until completely dissolved to obtain a dark brown solution. Weigh 2.5g hollow glass microspheres into a 50mL alumina crucible, transfer the above dark brown solution to the crucible, mix the hollow glass microspheres and solution evenly with a glass rod, and place in a muffle furnace at 600℃ for 30min. After the system cools naturally to room temperature, a black foamy product is obtained, which is ground and sieved using a 120-mesh standard sieve to obtain hollow microspheres A.

[0051] Hollow microspheres A were reduced at high temperature in a 5% H2-95% Ar atmosphere, heated to 650℃ at a rate of 10℃ / min, and held for 4 hours to obtain hollow microspheres B.

[0052] 0.20 g of the hollow microspheres B and 0.04 g of sublimed sulfur were weighed and mixed thoroughly. A sulfidation reaction was then carried out in an Ar atmosphere at a temperature of 400 °C, a heating rate of 2 °C / min, and a holding time of 2 h to obtain the target product, glass / sulfide composite hollow microspheres. A single-sphere scanning electron microscope image is shown below. Figure 3 As shown, its cross-sectional scanning electron microscope image is as follows. Figure 4 As shown, its XRD pattern is as follows. Figure 5 As shown in the figure, its absorption performance is as follows: Figure 6 As shown.

[0053] The glass / sulfide composite hollow microspheres prepared according to the above method have an average sulfide composite shell thickness of 350 nm, and their chemical composition includes Co8FeS8, FeS, Co9S8, FeCoS2, SiO2, and amorphous silicates, with a density of 0.72 g / cm³. 3 The isostatic confining pressure withstand strength (maximum test pressure with a volume survival rate of over 90%) is 25.9 MPa. With a mass filling ratio of 50%, the absorption bandwidth is 4.54 GHz (13.46-18.00 GHz) at a thickness of 1.7 mm, and the maximum reflection loss at 6.72 GHz is -32.06 dB at a thickness of 3.5 mm.

[0054] Example 2-10

[0055] The specific implementation steps are as described in Example 1, and the specific differences are shown in Table 1.

[0056] Table 1

[0057]

[0058] Examples 11-19

[0059] The specific implementation steps are as described in Example 1, and the specific differences are shown in Table 2.

[0060] Table 2

[0061]

[0062] Examples 20-22

[0063] The specific implementation steps are as described in Example 1, and the specific differences are shown in Table 3.

[0064] Table 3

[0065]

[0066] Examples 23-28

[0067] The specific implementation steps are as described in Example 1, and the specific differences are shown in Table 4.

[0068] Table 4

[0069]

[0070] The performance of the samples prepared in the above embodiments is shown in Table 5 below.

[0071] Table 5

[0072]

[0073] Test method:

[0074] Density and strength testing of glass / sulfide composite hollow microspheres:

[0075] Density was tested using Archimedes' principle. Strength was evaluated using isostatic pressing, and the test was conducted in accordance with the patent "A method for determining the isostatic pressing strength of hollow glass microspheres" (201410196976.0).

[0076] Electromagnetic property testing of glass / sulfide composite hollow microspheres:

[0077] Glass / sulfide composite hollow microspheres were mixed with paraffin at a mass ratio of 30%-75% to form coaxial rings. The rings had an inner diameter of 3 mm, an outer diameter of 7 mm, and a thickness of 2 mm. Electromagnetic parameters were then tested using a vector network analyzer to analyze their electromagnetic performance. The effective absorption bandwidth was found to be within the frequency range where reflection loss was ≤-10 dB.

[0078] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description. It is impossible to exhaustively list all the implementation methods here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.

Claims

1. A lightweight, high-strength composite microwave absorbing material, characterized in that, The composite microwave absorbing material is a hollow microsphere; Its structure includes hollow glass microspheres and a metal sulfide composite shell bonded to the hollow glass microspheres; The interface between the hollow glass microspheres and the metal sulfide composite shell is partially fused. The preparation method of the composite absorbing material includes the following steps: Metal salts and organic fuels are dissolved in deionized water, hollow glass microspheres are added, and the mixture is stirred evenly to obtain a precursor solution. The above precursor liquid was placed in a high-temperature muffle furnace for combustion reaction, and hollow microspheres A were obtained by sieving. The hollow microspheres A were calcined in a reducing atmosphere to obtain hollow microspheres B; The hollow microspheres B were mixed evenly with sulfur powder and calcined in an inert atmosphere to obtain the composite microwave absorbing material. The metal salt is an organic or inorganic salt of a metal; The concentration of the metal salt in the precursor solution is 2-15 mol / L; The molar ratio of the organic fuel to the metal salt is 1-4; The organic fuel is selected from one or more of citric acid, glycine, urea or ethylene glycol; The mass concentration of the hollow glass microspheres is 0.35-1.5 g / mL; During the process of placing the precursor liquid in a high-temperature muffle furnace for combustion reaction to form hollow microspheres A, the combustion reaction process promotes the partial fusion of the interface between the final product hollow glass microspheres and the metal sulfide composite shell, without a clear boundary line.

2. The composite absorbing material according to claim 1, characterized in that, The density of the hollow microspheres is 0.4-1.5 g / cm³. 3 Particle size 6-120 micrometers; and / or The hollow glass microspheres have a silicate glass shell with a thickness of 200-1200 nanometers; and / or The thickness of the metal sulfide composite spherical shell is 20-1000 nanometers.

3. The composite microwave absorbing material according to claim 1 or 2, characterized in that, The metal sulfide composite spherical shell contains a metal component selected from one or more of iron, cobalt, nickel, copper, or molybdenum.

4. The composite absorbing material according to claim 1, characterized in that, The combustion reaction takes place in an air atmosphere, at a temperature of 300-800℃, and for a time of 5-40 minutes.

5. The composite absorbing material according to claim 1, characterized in that, The sieving process uses a 35-350 mesh standard sieve.

6. The composite absorbing material according to claim 1, characterized in that, The calcination temperature in a reducing atmosphere is 500-700℃, and the holding time is 1-5h.

7. The composite absorbing material according to claim 1, characterized in that, The mass ratio of sulfur powder to hollow microspheres B is 1:20-1:

3.

8. The composite absorbing material according to claim 1, characterized in that, The calcination in an inert atmosphere is carried out at a temperature of 200-700℃ for 2-4 hours.

Citation Information

Patent Citations

  • Method for measuring isostatic pressure resistance of hollow glass beads

    CN103954506A

  • Hollow multilayer core-shell material with electromagnetic wave adsorption characteristic and preparation method thereof

    CN102504758A

  • Method of coating glass hollow microsphere surface with spinel type ferrite shell, obtained hollow composite microsphere and application thereof

    CN106512874A